PEDAGOGICAL FOUNDATIONS OF STEAM APPROACH IN CAREER CHOICE (IN THE CONTEXT OF PRIMARY EDUCATION) - kizi, Salokhitdinova Navruza Muradulla (PT. Antis International Publisher, 2025)
Objective: This study investigates the pedagogical foundations of the STEAM approach in influencing career choices in primary education, particularly within Uzbekistan’s educational context. Method: Employing a qualitative analysis that integrates project-based and problem-based learning methodologies, the research explores how experiential learning bridges theoretical constructs and practical applications. Results: Findings indicate that early exposure to STEAM disciplines significantly enhances students’ professional orientations by fostering creativity, critical thinking, and problem-solving skills, while also emphasizing the role of policy initiatives in embedding STEAM principles into the national curriculum. Novelty: This research offers a novel perspective by directly linking STEAM pedagogy to career development outcomes in early education, thereby addressing a critical gap in current literature and providing actionable insights for curriculum design, teacher training, and educational policy reform.